Oil palm empty fruit bunch composite / Rosmawati Abd. Kahar - Abd. Kahar, Rosmawati (2004)
Composite is defined as a structural material, which consists of combining two or more constituents. The constituents are combined at a macroscopic level and are not soluble in each other. One constituent is called the reinforcing phase and the one in which it is embedded is called matrix. The reinforcing phase material may be in the form of fibres, particles or flakes which can be used either natural or recycle material. The matrix phase material is generally continuous such as metal, ceramic and plastic. Composite offer several other advantages over conventional materials. These may include improved strength, stiffness, fatigue and impact resistance, thermal conductivity, corrosion resistance, etc. Besides, it has low mass properties compared to metal material, which requires in technology today especially in aerospace industry. Composite' s market price more cheaper than steel.